Replisome dynamics and use of DNA trombone loops to bypass replication blocks(,) - Yao, Nina Y. (2008)
Replisomes are dynamic multiprotein machines capable of simultaneously replicating both strands of the DNA duplex. This review focuses on the structure and function of the E. coli replisome, many features of which generalize to other bacteria and eukaryotic cells. For example, the bacterial replisome utilizes clamps and clamp loaders to coordinate the actions required of the trombone model of lagging strand synthesis made famous by Bruce Alberts. All cells contain clamps and clamp loaders and this review summarizes their structure and function. Clamp loaders are pentameric spirals that bind DNA in a structure specific fashion and thread it through the ring shaped clamp. The recent structure of the E. coli β clamp in complex with primed DNA has implications for how multiple polymerases function on sliding clamps and how the primed DNA template is exchanged between them. Recent studies reveal a remarkable fluidity in replisome function that enables it to bypass template lesions on either DNA strand. During these processes the polymerases within the replisome functionally uncouple from one another. Mechanistic processes that underlie these actions may involve DNA looping, similar to the trombone loops that mediate the lagging strand Okazaki fragment synthesis cycle.